Analisis Manajemen Mutu Laboratorium IPA di Madrasah Tsanawiyah Negeri 4 Jombang - Hisbulloh Huda; Abdelhameed Mohammed Al-Badrawy Al-Ramzy; Muhammad Faizur Rahman (Yayasan Bayt Shufiya Nusantara, 2026)
This study aims to analyze the quality management of science laboratories at Madrasah Tsanawiyah Negeri (MTsN) 4 Jombang. A qualitative approach with a descriptive-analytical design was employed. Data were gathered through interviews with the laboratory head and science teachers, supplemented by journal articles, theses, websites, laboratory work program documents, and Standard Operating Procedures (SOPs). Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that the quality management of the science laboratory at MTsN 4 Jombang is structured around four primary dimensions: planning, organizing, implementing, and supervising. Planning is demonstrated by the formulation of work programs, usage schedules, and pre-practicum SOPs. Organizing is reflected in the distribution of roles among the headmaster, laboratory head, laboratory assistants, science teachers, and students. Practicum implementation is supported by equipment usage procedures, laboratory rules, utilization administration, and occupational safety regulations. Supervision is carried out through activity logging, equipment inspection, damage reporting, and occupational health and safety (OHS) risk management. Nonetheless, laboratory management still faces constraints related to facility availability.